Diagnostic Dilemma During Laparoscopic Cystectomy of Twisted Serous Cystadenofibroma of Ovary in Adolescent Girl – A Case Report with Literature Review - Kayastha, Suresh; Paudel, Jamuna Kiran; Deo, Rajiv; Joshi, Hari Om; Thapa, Sweta (Med Phoenix, 2022)
The most ovarian tumor arises from the surface epithelium and the serous tumor is the most common histological variant. Serous cystadenofibroma is a rare variant of serous tumor that comprises both epithelial and fibrous stromal components. They are benign in nature but may often be misinterpreted as malignant nature due to their solid cystic nature with papillary projections. We herein report a case of twisted right ovarian cyst in 17 years unmarried girl that was clinically and radiologically benign and hence managed laparoscopically. Intraoperatively cyst ruptured that released clear serous fluid. During cystectomy, multiple small to large size (maximum 2x2 cm) papillary projections were noted within the uninoculated cyst without any other solid components. With the possibility of a borderline tumor, the patient party was counseled and opted for cystectomy with the possible need for a second surgery. The final histopathology report was benign serous cystadenofibroma.